Electron and phonon dynamics in indium antimonide crystals - Brazis, Romuald; Raguotis, Romas (Optical and quantum electronics, 2008)
Monte Carlo method is used for the study of electron and phonon dynamics in InSb crystals in the steady electric field. If the lattice temperature is significantly lower than the Debye temperature, and the lifetime of phonons is finite, their accumulation (especially LO ones) is found to occur in a limited range of momentum space. Accumulated phonons are shown to affect the values of electron drift velocity and mean energy. The values are subject to continuous increase in the time of ballistic flight upon step-like switching-on electric field, and subsequent decaying oscillations before accessing the stationary state. In contrast to these, the transient response of LO phonon number shows an abrupt increase after a picosdecond-scale delay, with a trend to subsequent saturation. Phonon band population inversion is discussed in relation to possible stimulated emission of photons.